Social Media have Changed Self and Privacy - Yang, Junhan (Transactions on Social Science, Education and Humanities Research, 2023)
With the advent of social media, people’s lifestyles have changed. According to this phenomenon, the presentation and recognition of the self, the display and exposure of privacy have all changed. To begin with, this paper briefly introduces the concepts of social media, self, and privacy by using Carr, Hayes, Herbert, Goffman, Minan, and so on. After that, the paper turns to the core part, which mainly deepens the change of self and privacy through the change of communication mode. And in this part, which uses examples to demonstrate the change of self and privacy. For example, statistical experiments on the number of social media participants from 2005 to 2019, the global growth trend of people using social media network platforms, and the number of online active people on social media platforms. Finally, the specific changes in social media regarding various aspects of self and privacy are expounded. The conclusion is that social communication is changing as people use social media platforms to share information. Social platforms help individuals present themselves broadly and learn more about others’ selves. What’s more people’s privacy has become more open. These changes have profoundly affected people’s lives. Therefore, people should make reasonable use of social media to make social media better promote the development of society.